2012
DOI: 10.1364/ao.51.001459
|View full text |Cite
|
Sign up to set email alerts
|

Passive long-range surface plasmon-polariton devices in Cytop

Abstract: Passive elements operating with long-range surface plasmon polaritons and constructed as Au stripes embedded in Cytop were investigated theoretically and experimentally at wavelengths near 1310 nm. The elements investigated consist of straight waveguides, S-bends, Y-junctions, couplers, and Mach-Zehnder interferometers. The measured performance of these devices is close to theoretical expectations, although uniformity issues were noted, likely because of fabrication imperfections. Cytop is a low-index polymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
(53 reference statements)
2
16
0
Order By: Relevance
“…The slope of Eq. (3a) was extracted by fitting and found to be m 1.35 rad∕mW, which is close to the value obtained in the previous case (m 1.25 rad∕mW, previous subsection); fabrication inconsistencies among structures and waveguide deformation could be causes for the discrepancy [19,20]. Again, it is observed that at a dissipated power of ∼12 mW (5 mA injected current), the measurements deviate from sinusoidal, probably for the same reasons as discussed in the previous subsection.…”
Section: Experiments On 30 MM Long Mzissupporting
confidence: 86%
See 4 more Smart Citations
“…The slope of Eq. (3a) was extracted by fitting and found to be m 1.35 rad∕mW, which is close to the value obtained in the previous case (m 1.25 rad∕mW, previous subsection); fabrication inconsistencies among structures and waveguide deformation could be causes for the discrepancy [19,20]. Again, it is observed that at a dissipated power of ∼12 mW (5 mA injected current), the measurements deviate from sinusoidal, probably for the same reasons as discussed in the previous subsection.…”
Section: Experiments On 30 MM Long Mzissupporting
confidence: 86%
“…7 and compared with Eq. (3d), in which the value used for the input power was P in 1.83 mW, the attenuation was α 0.691 mm −1 (mode power attenuation of 6 dB∕mm), the total radiation coefficient was ρθ 0 0.039 (total radiation loss 0.34 dB), the total transition coefficient was τ 0 0.599 (total TL 5.2 dB), and the nominal phase shift between the arms was ϕ 0 −02π, all adjusted by optimizing the fit between the theoretical and experimental responses, with α, ρθ 0 , and τ 0 remaining very close to modeling results reported in [20]. The slope of Eq.…”
Section: B Experiments On 38 MM Long Mzissupporting
confidence: 65%
See 3 more Smart Citations